From Nearly Zero Energy to Carbon-Neutral: Case Study of a Hospitality Building - Francesco Causone (MDPI AG, 2021)
In recent years, many cities around the world have pledged to upgrade their building stocks to carbon-neutral. However, the literature does not yet provide a shared definition of carbon-neutral building (CNB), and the assessment objectives and methodological approaches are vague and fragmented. Starting from the available standards and scientific literature on life cycle assessment (LCA), this paper advances an operational definition for CNB on the basis of an explicit calculation approach. It then applies the definition to an urban case study, comparing it against a state-of-the-art nearly Zero Energy Building (nZEB) scenario, with the intent of highlighting the major practical limitations connected to the application of a methodologically sound carbon neutrality calculation. The case study shows that carbon neutral objectives can hardly be achieved by single urban buildings because of the lack of spaces that can provide onsite carbon offsetting actions. Carbon neutrality may be better approached at the city, regional, or national scales, where overarching policies may be defined.